(untitled) (American Journal of Islam and Society, 2014)
This special academic event was organized by the Sociology of Religion (Socrel) Study Group of the British Sociological Association in London on December 7, 2013. One of its main objectives was to discuss, in the light of negative publicity and the increasing number of Muslim students pursuing certain professions, whether “Islam” as a module or a course has been adequately woven and integrated into the university teaching and learning contexts. The organizers, Socrel chair Abby Day (Department of Sociology, Goldsmiths, University of London) and Sarah-Jane Page (School of Languages and Social Sciences, Aston University), sought answers to the following questions: To what extent are higher education institutions responding to this relationship? How do Muslim students feel that Islam is represented in higher education? Does a Christianized curriculum still dominate the way these courses are designed? How do non-Muslim students respond to the content of courses that mainly deal with Islam and Muslims? How do teachers respond to a more diverse student body that hails from various socio-cultural backgrounds? Sociologists of religion have realized the importance of reflecting critically upon the study and teaching of religion. Publications such as Robert Orsi’s edited The Cambridge Companion to Religious Studies (New York: Cambridge University Press, 2012) has paid attention to these and related aspects. A qualitative shift of scholary endeavors has been noted; scholars and researchers have now turned their lenses to specific religious traditions that have come under the spotlight because of their adherents’ apparent “violent” acts. Since 9/11, Islam and Muslims have naturally become one of the targeted traditions (see “The Muslim World after 9/11,” Rand report at www.rand.org). This scholarly attention has resulted in the spread of Islamophobia in western Europe and elsewhere, not to mention the gradual securitization of Muslim communities. This latter development seems to have enormous implications for the academic arena where courses/modules on aspects of “Muslim extremism” in countries such as the United Kingdom have been closely watched and ...